Experience with P. Falciparum Malaria in a tertiary care hospital in Bangladesh - Rahman, M Monzur; Ali, M Zulfikar; Akhteruzzaman, M (KYAMC Journal, 2013)
DOI: http://dx.doi.org/10.3329/kyamcj.v1i1.13298 KYAMC Journal Vol.1(1) July 2010, 1-2